PENGEMBANGKAN BUDAYA TOLERANSI DAN DAMAI: PERSPEKTIF ISLAM DALAM MUAMALAH EKONOMI - Sabrina Camila Octavia; Sahid Anabah; Slamet Riyadi; Rizal Maulana (STKIP Subang, 2024)
A culture of tolerance and peace are important principles in the current global context, especially in increasingly complex economic interactions. In the Islamic context, economic muamalah not only includes aspects of material transactions, but also emphasizes the importance of moral and ethical values in every economic interaction. This article examines how Islamic values of tolerance and peace are applied in economic matters, with a focus on the ethical principles that guide behavior in transactions. The discussion included the importance of justice, transparency and mutual respect in building harmonious economic relations. This research uses a library study method to collect information from books, journals and other relevant references. The results show that the culture of tolerance in Islamic economics plays a key role in reducing social conﬂict and promoting peace between religious communities. The practical implication of this research is the importance of implementing Islamic principles in economic matters to create an inclusive and sustainable business environment, where the values of tolerance and peace become the main foundation in global economic interactions. Keywords: Tolerance, Peace, Muamalah Islamic Economics, Economic Ethics, Culture of Tolerance